Global, regional, and national burden of intracerebral hemorrhage in adolescents and young adults and its predictions: a systematic analysis of the Global Burden of Disease Study 2021 - Hao, Guangzhi; Han, Yuwei; Liang, Yong; Zhang, Bingying; Dong, Yushu; Liang, Guobiao (Frontiers in Neurology, 2025)
ObjectiveThis study analyzes the global, regional, and national burden of intracerebral hemorrhage (ICH) in adolescents and young adults using data from the Global Burden of Disease Study 2021. ICH in younger populations impacts cognitive and physical health, hindering educational and professional development. This research provides insights into ICH trends, burden distribution, and future projections to support targeted public health strategies.MethodsWe extracted age-standardized incidence, mortality, and disability-adjusted life years (DALYs) data for ICH from 1990 to 2021, stratified by age, sex, and Socio-demographic Index (SDI). Estimates were generated using the DisMod-MR 2.1 Bayesian meta-regression framework. Temporal trends were analyzed, and decomposition analysis was performed to quantify the contributions of population growth, aging, and epidemiological changes to the evolving ICH burden. Frontier analysis was used to evaluate the performance of countries relative to their SDI levels. Forecasts of ICH burden through 2044 were produced using the Nordpred age-period-cohort model, with internal validation and sensitivity analyses conducted to assess model robustness.ResultsFrom 1990 to 2021, global age-standardized ICH incidence, DALYs, and mortality rates declined, though absolute cases, deaths, and DALYs rose in low- and middle-SDI regions. High-SDI areas showed the most substantial burden reductions, while Oceania and Sub-Saharan Africa exhibited higher rates due to limited healthcare resources. Projections suggest further declines in age-standardized DALYs and mortality, though incidence may rise by 2044.ConclusionDespite declining age-standardized rates, absolute ICH burdens continue to grow in low-SDI regions, underscoring the need for tailored public health policies and resource allocation to reduce ICH disparities in young populations, especially in underserved regions. Equitable healthcare resources and targeted interventions are essential for reducing global ICH disparities and improving outcomes.